CAMPUR KODE BAHASA GAUL MAHASISWA DALAM PEMBELAJARAN BAHASA INDONESIA - Ratna Juwita, Silvia; Wan Minto, Deri; Oktian Fajar Nugroho; Febrianti, Nurul (UNIB Press, 2022)
The purpose of this study was to describe the code mixing of student slang at universities in Indonesian language courses, especially Esa Unggul University. This type of qualitative research and descriptive method of analysis. The process of collecting basic and advanced technical data is insertion, intrusion, or insertion techniques. The data before being analyzed is verified first, then analyzed. Validation is done by triangulation technique through internal and external validation. The results found that many students use mixed language, especially writing. It is better for lecturers to give warnings both directly in class, and in writing through scientific writing, and provide intensive counseling so that the younger generation does not lose their national identity. Keywords: Code Mixing, Student Language, Language Learning